Nanoencapsulação de luteína e avaliação in vivo da sua influência sobre a memória - Silva, Jessica Thaís do Prado (2017)
Carotenoids are a group of fat-soluble pigments presenting numerous benefits to human health. Among them, lutein, a yellow-orange xanthophyll, has attracted attention due its biological activity. Since the human body is unable to synthesize carotenoids, lutein acquisition is only possible through food or supplementation. Lutein rich diets have been associated with the improvement of cognitive functions in adults. However, the chemical structure of lutein, which is responsible for its beneficial effects, is extremely sensitive to heat, low pH, dissolved oxygen and exposure to light. Encapsulation is a technique that has proved effective in protecting bioactive compounds against external agents and increased bioavailability in the body, allowing such compounds to reach its absorption site. This study aimed to obtain and characterize lutein nanoencapsulated in biodegradable polymers, perform the analytical validation of a UV-Vis procedure to determine the lutein concentration in the nanoparticles and to evaluate the effect of encapsulated lutein on declarative memory of mice. Lutein was successful encapsulated in zein and polyvinylpirrolidone matrix, separately, allowing obtaining nanometric and spherical particles. In the first part of this work, an analytical procedure for lutein determination in zein nanoparticles was validated presenting quantification limit of 4.407 mg.L-1, which is a sufficient parameter to calculate entrapment efficiency in nanoparticulate systems. In the second part of this work, lutein encapsulation in PVP nanoparticles was able to increase 43 times lutein water solubility and its oral administration to mice (10 mg.Kg-1and 1.5 mg.Kg-1), during 14 days presented effect 66 higher than pristine lutein on mice’s declarative memory during object discrimination task. This technique showed to be a viable alternative to increase lutein water solubility and, consequently, its bioavailability, contributing with lutein’s role in cognitive impairment.